A new model for collection of clinical outcomes data in patients with chronic rhinosinusitis. Issue 5 (15th January 2014) - Meier, Josh C.; Remenschneider, Aaron K.; D'Amico, Laura; Holbrook, Eric H.; Gray, Stacey T.; Metson, Ralph
<x xml:space="preserve">Abstract</x> Background The need for objective assessment of patient outcomes is becoming an essential component of clinical practice for both private and academic otolaryngologists. The purpose of this study is to describe the implementation of an online model for collection of clinical outcomes data in patients with chronic rhinosinusitis (CRS). Methods Patients completed the Sinonasal Outcome Test (SNOT‐22), Chronic Sinusitis Survey (CSS), and EuroQol 5‐dimension assessment (EQ‐5D), before and after sinus surgery. One year after initial patient enrollment, an online tool was developed to facilitate collection of postoperative data. Response rates preimplementation and postimplementation of online data collection were compared. Results A total of 520 sinus surgery patients provided outcomes data from the practices of 7 private practice (n = 308) and 4 academic otolaryngologists (n = 212). With implementation of the online collection instrument, the response rate at 3 months increased from 67% to 78.8% (p = 0.004). The overall follow‐up rate at 3 months was higher in patients recruited from private as compared to academic practices (77.9% vs 69.8%, respectively, p = 0.04). Conclusion Quality of life data can be effectively collected from CRS patients in both the private and academic practice setting. The addition of an online data collection tool can significantly increase response rates, and allow a comprehensive capture of meaningful clinical outcomes. Such a model is not difficult to implement and has increasing relevance as payers begin to request outcome data from providers.